DEVELOPMENT OF AN ENZYME IMMUNOASSAY DIAGNOSTIC TEST FOR DETECTION OF FIRE BLIGHT PATHOGEN Erwinia amylovora - Azhіmahan , M.A.; Varisev, U.A.; Drenova , N.V.; Khasanov , V.T.; Dzhaymurzina , A.A.; Tuleeva , A.K.; Umiralieva , Zh.Z. (Eurasian Journal of Applied Biotechnology, 2016)
We designed a test system for the immunofermental analysis of Erwinia amylovora, the causative agent of fire blight in fruit crops. We isolated bacteria from fruit samples cultivated in the Uigur district of Almaty, Kazakhstan. For the selection of causative agent to the studied bacterium on different nourishing environments, the best a Levanovaya environment appeared of environments further is an environment of КingaB In and potato agar. We isolated bacteria and identified their species, using real-time polymerase chain reaction (RT-PCR). Immunization of laboratory animals’ suspension of bacterial cages was carried out (anti-gene). For the receipt of specific antiserums used the strain of СFBP 1430 (Bielefeld, France, isolated в1972, author SamsonR.) from collection of E. amylovora FGBU ‘VNIIKR’.Antiserum with a specific caption 1: 107 in ELISA was received. Erwinia amylovora specific for immunoglobulin from which they were emitted and conjugates of antibodies with high cleaning peroxidase of horseradish were prepared. The sandwich ELISA exhibited a sensitivity of 8 x 104 cells/mL, which exceeds the sensitivity of the commercial analog. Test systems were compared based on their sensitivity and specificity to various strains of E. amylovora, isolated from the Russian Federation, Kyrgyzstan, Kazakhstan, Moldova, Poland, and France, as well as other species of the genus Enterobacteriaceae from FGBU ‘VNIIKR’.The strain CFBP 1430 was used as a control.